Pengaruh Penerapan Media Youtube Terhadap Hasil Belajar Fisika Mahasiswa Semester IV STKIP Muhammadiyah Sungai Penuh - Desrianti Sahida (Peneliti.net, 2023)
The purpose of this study was to determine the knowledge competence of students before using YouTube media in Physics learning, to determine students' knowledge competence after using Youtube media in Physics learning, and to find out the increase in students' knowledge competence after using Youtube media in Physics learning. This research methodology is a quantitative research using an experimental approach. While the design of the pre-experimental design (pre-experimental design). The research design used in this experimental research is One Group Pretest-Posttest. The results of the research on assessing the knowledge of students 79% of the number of students have mastered more than 70% of the learning objectives that have been set with an average value of 76. This shows the success of students in finding problems and solving Physics problems in the youtube learning media used . In addition, the application of YouTube learning media has also succeeded in guiding students in mastering the material by fully involving students in the learning process. The influence of students' Physics learning outcomes between pretest and posttest results is due to the treatment given by applying YouTube media in the Physics learning process. As long as the treatment is given by applying YouTube media, students are seen to be more active in participating in the Physics learning process, especially when doing practicum.